2017
DOI: 10.5296/jpag.v7i3.11451
|View full text |Cite
|
Sign up to set email alerts
|

Measurement the Performance Levels of Islamic Banks in Jordan

Abstract: For now, there are incomplete studies to investigate the Jordan Islamic banks' (IBs) performance. Also, there is evidence of increasing withdrawal of investors from IBs to commercial banks as a result of decreased confidence among depositors and minimize of profits. This study focuses on using secondary data analysis to measure the performance of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The Cronbach's alpha was used to evaluate the index's dependability. According to Hair et al (2006) and Qasim et al (2017), acceptable values range from 0.60 to 0.70. The Cronbach's alpha score of 0.898 in this study's overall index suggested that it had acceptable reliability (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The Cronbach's alpha was used to evaluate the index's dependability. According to Hair et al (2006) and Qasim et al (2017), acceptable values range from 0.60 to 0.70. The Cronbach's alpha score of 0.898 in this study's overall index suggested that it had acceptable reliability (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous literature contains a number of studies that investigate the green human resources on different issues in Jordan such as healthcare and education but to the knowledge of the researcher, there is no study that investigates the impact of green human resources management in the Jordanian government institutions (Qasim et al, 2017). As a result, a comprehensive paper is required to consider the limitations of previous research in order to improve and update the research on green human resources in Jordan, as well as to include some recent variables that have not been addressed by previous studies and articles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this process, the measurement of performance levels on Islamic banking can determine their performance measurement and monitoring system (Antonio, Sanrego and Taufiq, 2012). The performance of Bank is important for all parties; depositors, bank managers, regulators, and competitive markets (Qasim et al, 2017). The performance of the bank provides a signal for investors-depositors withdraw funds from an investment or withdraw funds from the bank (Qasim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The performance of Bank is important for all parties; depositors, bank managers, regulators, and competitive markets (Qasim et al, 2017). The performance of the bank provides a signal for investors-depositors withdraw funds from an investment or withdraw funds from the bank (Qasim et al, 2017). Conventional banks and Islamic banks in their role as financial institutions compete for clients and investors (Rabaa and Younes, 2016).…”
Section: Introductionmentioning
confidence: 99%